OPERATOR ⊞A and ⊠A ON INTUITIONISTIC FUZZY RING - Dian Pratama (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2020)
Intuitionistic fuzzy sets is a sets that are characterized by membership and non-membership function which sum is less than one. When applied to ring theory, it will called intuitionistic fuzzy rings. The fuzzy set operator is a mapping between the membership function and the interval [0,1]. In this study, we will describe properties of operator and in intuitionistic fuzzy rings. The characteristics that will be studied include the structure of and if A is an intuitive and fuzzy ring and vice versa.